Analisis Self Efficacy Dan Tingkat Stress Siswa Di Pondok Pesantren Al-Azzam Babat Supat - Nurlaila; Abdur Razzaq; Neni Noviza (Social Science and Contemporary Issues Journal, 2023)
This research aims to determine the self-efficacy and stress levels of students at the Al-Azzam Babat Supat MUBA Islamic Boarding School. This research use desciptive qualitative approach. Data collection tools in this research are observation, interviews and documentation. The subjects of this research were students and administrators of the Al-Azzam Babat Supat Islamic Boarding School. The data analysis techniques in this research are data reduction, data display, and conclusion drawing. The results of the research stated that the self-efficacy of students at the Al-Azzam Babat Supat MUBA Islamic Boarding School varied or varied and the students' self-efficacy was sufficient, namely in completing tasks on time. Based on the research results, it can be concluded that the stress level of students at the Al-Azzam Babat Supat MUBA Islamic Boarding School is relatively low and still reasonable. There have not been any students who are very tired, like fainting in the hut because they are tired. There are no students at the Al-Azzam Babat Islamic Boarding School who are disturbed in their demands for knowledge at the Al-Azzam Babat Islamic Boarding School. Symptoms shown by students when experiencing mild stress at the Al-Azzam Babat Islamic Boarding School are decreased concentration when studying, such as intoxication and less attention to the teacher when explaining the material. Social relations between students at the Al-Azzam Babat Islamic Boarding School are very good. There are no students who have difficulty carrying out their activities, everyone is able to get to know each other. The causes also vary, such as fear of studying because of the possibility of being tired after a day's activities. There are no students at the Al-Azzam Babat Islamic Boarding School who experience severe stress. The stress experienced by students when there are tasks such as rote assignments that they cannot memorize well. Even that is still normal